2005
DOI: 10.1002/humu.9375
|View full text |Cite
|
Sign up to set email alerts
|

The human TBX5 gene mutation database

Abstract: Germline mutations of the TBX5 gene were identified as the primary cause in up to 70 % of patients with Holt-Oram syndrome (HOS), an autosomal dominant disorder characterized by malformations of the upper limbs and cardiac defects. Furthermore, somatic mutations of the TBX5 gene have been described in diseased heart tissues of patients with congenital heart defects of different cause. The relationship between genotype and phenotype remains unclear and the underlying mechanism of the pathogenic effect is not so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 16 publications
1
35
0
Order By: Relevance
“…Most of the previously known mutations in the TBX5 gene are truncating mutations (deletions, missense, nonsense, splice site and frameshift mutations), which result in haploinsufficiency of the TBX5 protein [Gruenauer-Kloevekorn and Froster, 2003;Heinritz et al, 2005;McDermott et al, 2005]. The present finding confirms a previous report by Böhm et al [2008] describing a single patient with HOS carrying a similar TBX5 frameshift mutation (c.1333delC, p.H445fsX136) predicted to result in an elongated and miscoded TBX5 protein.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Most of the previously known mutations in the TBX5 gene are truncating mutations (deletions, missense, nonsense, splice site and frameshift mutations), which result in haploinsufficiency of the TBX5 protein [Gruenauer-Kloevekorn and Froster, 2003;Heinritz et al, 2005;McDermott et al, 2005]. The present finding confirms a previous report by Böhm et al [2008] describing a single patient with HOS carrying a similar TBX5 frameshift mutation (c.1333delC, p.H445fsX136) predicted to result in an elongated and miscoded TBX5 protein.…”
Section: Discussionsupporting
confidence: 81%
“…These mutations are spread throughout the coding exons of TBX5 [Heinritz et al, 2005], and most of the TBX5 mutations are known to be truncation mutations [Basson et al, 1997].…”
mentioning
confidence: 99%
“…This variable expressivity is observed even within families and suggests the existence of genetic and/or environmental modifiers. To date, over 50 different mutations in the Tbx5 locus have been identified in patients with Holt-Oram syndrome (17). Because many mutations lie within the coding region and result in a truncated or no protein, it has been proposed that Tbx5 haploinsufficiency may be the mechanism underlying Holt-Oram pathogenesis.…”
mentioning
confidence: 99%
“…In addition to mutations in the coding sequences, mutations in intragenic regions have been identified in patients with Holt-Oram syndrome (10,17). Furthermore, it has been suggested that unscreened mutations within introns or regulatory sequences of the Tbx5 locus may account for the relatively low (35%) detection rate in familial as well as sporadic cases of Holt-Oram syndrome (5).…”
mentioning
confidence: 99%
“…Moreover, Tbx5 expression pattern in the upper limb, atria, and left ventricle along with mouse genetics studies have strengthened the causative link between TBX5 and HOS (3). Over 70 mutations in the TBX5 locus have been identified so far in HOS patients (4). Many result in no protein production or in truncated proteins.…”
Section: Holt-oram Syndrome (Hos)mentioning
confidence: 99%